Pengaruh Intellectual Capital dan Struktur Modal terhadap Nilai Perusahaan dengan Profitabilitas sebagai Intervening pada Perusahaan Manufaktur Makanan dan Minuman di BEI - Riska Septi Ariani; Sri Rahayuningsih (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study aims to examine the effect of Intellectual Capital and Capital Structure on Firm Value with Profitability as an intervening variable in manufacturing companies within the food and beverage subsector listed on the Indonesia Stock Exchange. This research employs a quantitative approach using secondary data obtained from annual reports, selected through a purposive sampling technique. The data were analyzed using the Partial Least Square method to evaluate both direct and indirect relationships among the variables. The results indicate that Intellectual Capital has a positive and significant effect on Firm Value, yet it does not have a significant effect on Profitability. Capital Structure also shows a positive and significant effect on Firm Value, while it has a negative and significant influence on Profitability. Furthermore, Profitability does not significantly affect Firm Value, indicating that it cannot function as an intervening variable. Profitability is found to fail in mediating the relationship between Intellectual Capital and Firm Value, and likewise fails to mediate the relationship between Capital Structure and Firm Value. These findings highlight that Firm Value is primarily influenced directly by Intellectual Capital and Capital Structure, whereas Profitability does not play a meaningful mediating role within the model